ANALYSIS OF APBDES EFFICIENCY AND EFFECTIVENESS CASE STUDY : PAGERWOJO VILLAGE, KEC. LIMBANGAN, KAB. KENDAL - Andi Kurniawati; Lis Widowati (Universitas Islam Lamongan, 2022)
This research was conducted in July 2022 at the Pagerwojo Village Hall Office, Kec. Limbangan, Kab. Kendal. Currentl, the constraint in village finance is the unbalanced APBDes between revenue and expenditure. In the future period it must be carried out efficiently and effectively in accordance with what was previously planned. The purpose of this study is to determine whether the budget at the Pagerwojo Village Hall Office, Kec . Limbangan, Kab. Kendal can be said to efficient and to know the performance of this financial performance.The research method in this research report the author uses several research methods including the observation method where the author here makes general observations of operational activities carried out at the office, then uses the interview method, namely the method where this interview is conducted by the author to dig up more information. In office habits regarding operational steps in the office, for the author provides various accurate evidence and documents originating from the source of the research place.